Gender implications of the GAP and KJWA: AGNES pre-SB 50 strategy meeting on agriculture and food security - Masiko, Winifred K; Huyer, Sophia; Mungai, Catherine (2019)
In Africa, women play an important role in food production, both paid and unpaid, and use of natural resources, while also serving as key figures in communities and the family. In regards to climate change adaptation, women and men will have different preferences and priorities based on their vulnerabilities, access to financial and natural resources, and ability to use information and extension services. Gender, therefore, is an essential factor in understanding how individuals, households, and communities adapt and respond to climate change. Rural women are especially vulnerable to climate change due to dual effects of their reliance on natural resources for income and food security and male-outmigration.